Case Report: Arthroscopic treatment of cedell fracture, shepherd fracture, and avulsion fracture at the insertion of the calcaneofibular ligament - Zhang, Sitong; Li, Dejian; Wang, Qian (Frontiers in Surgery, 2025)
Talar fractures represent less than 1% of all fractures, and combined fractures involving the posteromedial and posterolateral talar processes along with a lateral process fracture are exceptionally rare. These fractures are considered severe injuries that may lead to prolonged disability and persistent pain. The intricate anatomical configuration and the proximity of nerves and blood vessels surrounding the talus present substantial challenges in the management of posterior talar process fractures. Surgical procedures in this area are rare, and inadequate treatment may lead to significant discomfort and limitations in daily functioning for patients. In this case report, we describe a 45-year-old male who experienced a fall from a 2-meter height, leading to persistent right ankle swelling for 6 days. Radiographs, CT scans, and 3D-CT reconstructions identified fractures involving the posteromedial and posterolateral talar processes, as well as an avulsion fracture at the calcaneofibular ligament attachment site. To the best of our knowledge, there are no previously documented reports of this combined injury. We conducted arthroscopically assisted reduction and internal fixation through a posterior approach utilizing Herbert screw. The patient underwent a 4-year postoperative follow-up, during which favorable fracture healing was observed. The objective of this report is to demonstrate that arthroscopy offers a well-defined surgical field, aids in reduction and internal fixation, and to suggest a novel treatment approach for this uncommon fracture pattern.